Factors Contributing to the Students’ Intention to Apply Mechatronic Technology after Graduation - Yusof, Suhaila; Abdullah, Nurul Hidayah Liew; Paimin, Aini Nazura; Zhu Yuying (Journal of Technical Education and Training, 2024)
Mechatronic Technology is a field of specialization that offers job opportunities in various sectors of industry. Demand for skilled and semi-skilled labour has increased over the years. However, there are still graduates who do not pursue careers in this field of study. Therefore, this study aimed to identify the factors contributing to the intention to apply mechatronic technology after graduation. This study applied a survey research design, using a questionnaire as the instrument to obtain quantitative data. Samples of this study were consisted of 90 Mechatronic Technology Certificate students from Industrial Training Institute (ITI) Bukit Katil and ITI Tangkak. Data were descriptively analyzed using mean scores and standard deviations. Multiple linear regression was used to identify the most dominant factor contributing to the student’s intention to apply Mechatronic Technology after graduation. The results showed that students’ perception levels of ease of use, technology usefulness and student behaviour intentions to apply mechatronic technology were high. The findings also demonstrated that ease of use of technology was the most dominant and significant factor to contribute to students’ intention to apply mechatronic technology after graduation. The impact of this study provides insight into the application of TAM Model to understand students’ acceptance of the technology in the TVET contexts.